2013
DOI: 10.1089/thy.2012.0608
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Prophylactic Central Neck Dissection on Short-Term Locoregional Recurrence in Papillary Thyroid Carcinoma After Total Thyroidectomy

Abstract: Group A was more likely to have postoperative RAI ablation, temporary hypocalcemia, and overall morbidity than group B. Temporary hypocalcemia was the major surgical morbidity in pCND and, when excluded, the overall morbidity appeared similar between the two groups. Although our meta-analysis would suggest that those who undergo TT + pCND may have a 35% reduction in risk of LRR than those who undergo TT alone in the short term (< 5 years), it remains unclear how much of this risk reduction is related to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(148 citation statements)
references
References 53 publications
(124 reference statements)
7
131
1
4
Order By: Relevance
“…However, the authors were unable to determine how much of this reduction was due to postoperative RAI ablation (71.7% vs 53.1%) and how much to potential selection bias in some of the studies examined. 12 The results of our retrospective study are in agreement with those studies which maintain that the avoidance of PCCLND in low-risk PTC patients does not alter the excellent outcome of these patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the authors were unable to determine how much of this reduction was due to postoperative RAI ablation (71.7% vs 53.1%) and how much to potential selection bias in some of the studies examined. 12 The results of our retrospective study are in agreement with those studies which maintain that the avoidance of PCCLND in low-risk PTC patients does not alter the excellent outcome of these patients.…”
Section: Discussionsupporting
confidence: 91%
“…11 Moreover, patients treated by means of total thyroidectomy and PCCLND, when compared to those treated only via total thyroidectomy, exhibited more complications, which included temporary or permanent hypocalcemia or recurrent laryngeal nerve dysfunction. 12,13 Studies suggest that the dose as well as the potential benefits of postoperative RAI administration in low-risk patients with differentiated thyroid cancer (DTC) is a matter of debate. Two randomized controlled multicenter trials have found that low-dose radioiodine ablation with 30mCi with recombinant TSH, when compared to higher doses of 100mCi RAI with thyroid hormone withdrawal, in low-to intermediate-risk DTC patients had similar outcomes of successful ablation within 1 year.…”
Section: 2mentioning
confidence: 99%
“…The optimal management of papillary thyroid cancer has remained controversial as the available data on the best approach for management are related to retrospective evaluations, large national registry studies, and meta-analysis but not randomized clinical trials (RCTs) [48][49][50]. Only RCTs are able to exactly determine the optimal treatment, such as extent of surgery, in PTC patients.…”
Section: Managementmentioning
confidence: 99%
“…The role of prophylactic central compartment lymph node dissection has been debated in the literature over the past few decades. Although its routine use increases the accuracy in tumor staging, there is no clear evidence that this procedure leads to a reduction in recurrence or mortality [28]. In order to limit surgical morbidity, many surgeons perform unilateral paratracheal prophylactic lymphadenectomy (including the cervical and upper mediastinal lymph nodes).…”
Section: Does Surgical Pathology Provide Reliable Information For Manmentioning
confidence: 99%